The Effect of Keroncong Music Arrangements on The Interest of The Keroncong Music for Keroncong Tujuh Putri Listeners - Seno Maulana; Harry Tjahjodiningrat; Kiki Sukanta (Cinematology: Journal Anthology of Film and Television Studies, 2022)
This journal talk about the existence of keroncong music in globalization and modern era nowadays. Keroncong music has been around in Indonesia since it was introduced by the Portuguese in the 16th century with their Fado music. The music is well received because it has no religious value in it (egalitarian). However, with the growth of music and globalization that make other music genres easy to find in Indonesia, the existence of keroncong is increasingly threatened. Some Indonesian musician give their effort to overcome the situation, one of the way is by arrange pop music to keroncong vibes. This is what Keroncong Tujuh Putri group music do. The way they drawn the audience attention to be attracted by keroncong music made the writer want to assess how effective the effort is. The data obtained as material from this research is sourced from the shared questionnaire result about keroncong arrangement and its connection with the interest of keroncong music itself to the Keroncong Tujuh Putri listeners.